FENOMENA CAMPUR KODE PADA KOMUNIKASI GEN Z ANALISIS WACANA DI MEDIA SOSIAL TIK TOK - Budiana, Nurchalistiani; Safitri, Safitri; Ratnasari, Hesty; Mustofa, Muhamad (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
The development of digital technology has brought about major changes in the way Generation Z communicates, especially through social media such as TikTok, which has become a platform for linguistic expression and cultural identity. This study aims to reveal the forms and functions of code-mixing in TikTok user interactions using Suwito's (1985) theory as the basis for analysis. The approach applied is descriptive qualitative with observation techniques of user posts and comments. The results of the study identify three main types of code-mixing, namely inner code-mixing, which affirms local identit, outer code-mixing, which indicates a global orientation, and hybrid code-mixing, which reflects linguistic creativity. These findings show that code-mixing serves not only as a communication tool but also as a strategy for building self-image and negotiating social identity in the digital space. Overall, Generation Z's code-mixing practices on TikTok reflect dynamic, creative, and adaptive language skills in response to globalization.